Optimizing the Intensity of Lifestyle Medicine Interventions: Similar Outcomes for Half the Sessions. (May 2017) - Morton, Darren P.; Kent, Lillian; Rankin, Paul; Mitchell, Brett; Parker, Karina; Gobble, John; Diehl, Hans
Lifestyle medicine interventions are typically intensive by design. This study explored the optimal "dosage" of a well-known lifestyle medicine intervention—the Complete Health Improvement Program (CHIP). A total of 2383 individuals (mean age = 61.0 ± 9.2 years; 34% males) participated in either an 8-session (N = 448) or 16-session (N = 1935) version of the CHIP intervention conducted over 4 weeks in community settings throughout North America. Both the 8- and 16-session groups experienced significant improvements in all the chronic disease risk factors measured. There was no difference between the changes experienced by the 8- and 16-session groups in lipid profile, fasting plasma glucose, or systolic blood pressure. The 8-session group experienced a significantly greater reduction in body mass (0.3 percentage points or 0.8 lbs, P < .01), but the 16-session group recorded a significantly greater reduction in diastolic blood pressure (2.8 percentage points or 2.2 mm Hg, P < .01). There was no clear difference between the outcomes achieved in 4 weeks by the 8- and 16-session versions of the CHIP lifestyle medicine intervention. This study suggests that the short-term outcomes achieved by a 16-session CHIP intervention can be achieved in half the number of sessions, which has implications from a resourcing and cost-effectiveness perspective.